Criminality and economic growth province in Indonesian - Nairobi Nairobi; Muhammad Afif Firdaus; Fadeli Yusuf Afif (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
The decline in economic growth, which is offset by the increasing number of people and the lack of availability of jobs, has caused more people to be affected and involved in non-crime activities based on the crime rate (CR). This study aims to analyze the effect of crime rates on provincial economic growth in Indonesia in 2011-2020. The variables used are economic growth, crime rates, investment, labor, and initial growth. The method used is the Fixed Effect Model. The results show that the higher the crime rate impacts the decline in economic growth, further increase in investment and labor will encourage economic growth. In contrast, the initial growth shows that the economy of poor provinces grows slower than rich provinces.